Prognostic factors for survival in transverse colon cancers - KÖSTEK, OSMAN (My University, 2022)
Background Transverse colon cancer (TCC) is a rare condition that accounts for 10% of all colon cancers. TCC was accepted more likely right-sided colon cancers. We aimed to investigate whether TCC differs from other colon tumors by using clinical, pathological, and molecular prognostic factors known to be important in colon cancer and if it differs in its own anatomical structure.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Onkoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOJİ VE HEPATOLOJİ; ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); GASTROENTEROLOGY & HEPATOLOGY; Gastroenteroloji; Hepatoloji; Gastroenterology; Hepatology; Transverse colon cancer; Prognosis; Survival; BRAF V600E; Pathological stage; COLORECTAL-CANCER; MICROSATELLITE-INSTABILITY; ADJUVANT CHEMOTHERAPY; PROXIMAL COLON; STAGE-II; FLUOROURACIL; MUTATION